Greening the Future: Why Landscape Restoration Matters Now More Than Ever - Anantha, K.H.; Singh, Ramesh; Garg, Kaushal K; Venkataradha, A.; Shukla, Ashok; Uttam, R.K. (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Across the world, land degradation is accelerating under climate change, putting nearly 3 billion people at risk. The UNCCD estimates that 24 billion tonnes of fertile soil are lost annually, while droughts have become longer, more frequent, and more damaging. As global demand for food, water, and biomass rises, drylands have emerged as frontline battlegrounds for climate resilience, water security, and sustainable development. Global drylands already host 44% of the world’s cultivated systems and support half of global livestock production. Yet they are disproportionately vulnerable to rainfall variability, shallow aquifers, soil nutrient depletion, and land-use pressures. Bundelkhand reflects these global stressors: erratic monsoons, hard-rock aquifers, and decades of soil degradation have pushed communities close to collapse. Nearly 30% of land has remained fallow in some areas, cropping intensity stagnated at ~110%, and more than 80% of people depend on climate-sensitive rainfed farming. As elsewhere in Africa and Central Asia, ecological decline triggers social distress. Seasonal water scarcity increases women’s drudgery; youth migrate to cities; and shrinking livestock systems erode traditional safety nets. These patterns mirror global hotspots of climate-induced livelihood erosion. India’s Bundelkhand region offers a powerful demonstration of how degraded dryland landscapes can be revived through integrated, science-based, and community-driven restoration. Since 2009, the Bundelkhand landscape rejuvenation programme has transitioned from scattered watershed works to a mature, ridge-to-valley, evidence-driven model that is now informing adaptation strategies in other Indian states and receiving international attention as a scalable dryland restoration blueprint.